In military personnel It was carried out under nilateral spinal-epidural anesthesia Assessment of blood hemostasis parameters and prevention of thromboembolic events during surgery and postoperative periods - Rakhmankulov E.J. Ph.D.; Associate Professor Mirrakhimova S.Sh. Ph.D.; Professor Avakov V.E. Chakganov O'.A. (Peerian Journals Publishing, 2025)
A comparative assessment of the effectiveness and safety of spinal and epidural anesthesia shows a number of disadvantages of epidural anesthesia. Based on the accumulated experience of 24 years, the advantages of spinal anesthesia can be summarized as follows: "No one knows of such a deep and widespread anesthesia with such a small amount of drug, with such low systemic toxicity, and with such effectiveness" [68; 590-597 -b]. While several studies on this issue have shown the qualitative advantages of spinal anesthesia, there are reports of numerous failures of epidural analgesia, manifested by lack of anesthesia, insufficiently widespread anesthesia, unilateral anesthesia, or inadequate blockade of several segments.
Keywords: Spinal and epidural anesthesia; unilateral spinal anesthesia; hemostasis